Reaction Time in Stutterers - Nataraja NP; Venkatesh CS; Jagadish A (Journal of All India Institute of Speech and Hearing, 1970)
In  many  studies  reaction  time has been found to be delayed in  stutterers. Many  of these  studies  have  used auditory  stimuli  to  obtain  reaction  time. The present  study was carried out to find  the possible  differences  in reaction  time for  auditory and visual stimuli. The reaction  time to auditory and visual stimuli in 10 stutterers and 10 normals were obtained. It was found that the reaction  time was delayed in stutterers  under both the conditions,  when compared with  normals. Further,  it was also found that the stutterers  were  slower  in  responding to visual stimuli than  to  auditory stimuli.